ASSIGNMENT AND MONITORING INFORMATION SYSTEM OF PRAKERIN STUDENTS BASED ON SMS GATEWAY WITH RASPBERRY PI - Andri Setiyawan (Universitas Sultan Ageng Tirtayasa, 2020)
This research is aimed to: (1) develop of assignment and monitoring information system of prakerin students based on SMS gateway with Raspberry Pi, and (2) reveal the quality of assignment and monitoring information system of prakerin students based on SMS gateway with Raspberry based on ISO 9126 on aspects of usability, functionality and portability.This development study refers to the Waterfall development procedure by Roger S. Pressman. The development design was grouped into five procedures, consisting of: (a) communication, (b) planning, (c) modeling, (d) construction and (e) deployment. The results of this research are: (1) development of assignment and monitoring information system of prakerin students based on SMS gateway with Raspberry Pi done by using web-based CMS Kalkun and (2) testing the quality level using ISO 9126 on usablity aspect results 85% (high) with alpha cronbach of 0.851 (good), functionality aspect yields 1 (good), and meets the portability aspect.